Dangers of hyperoxia - Singer, Mervyn; Young, Paul J.; Laffey, John G.; Asfar, Pierre; Taccone, Fabio Silvio; Skrifvars, Markus B.; Meyhoff, Christian S.; Radermacher, Peter (Critical care (London, England), 2021)
Oxygen (O 2 ) toxicity remains a concern, particularly to the lung. This is mainly related to excessive production of reactive oxygen species (ROS). Supplemental O 2 , i.e. inspiratory O 2 concentrations (F I O 2 ) > 0.21 may cause hyperoxaemia (i.e. arterial (a) PO 2 > 100 mmHg) and, subsequently, hyperoxia (increased tissue O 2 concentration), thereby enhancing ROS formation. Here, we review the pathophysiology of O 2 toxicity and the potential harms of supplemental O 2 in various ICU conditions. The current evidence base suggests that PaO 2 > 300 mmHg (40 kPa) should be avoided, but it remains uncertain whether there is an “optimal level” which may vary for given clinical conditions. Since even moderately supra-physiological PaO 2 may be associated with deleterious side effects, it seems advisable at present to titrate O 2 to maintain PaO 2 within the normal range, avoiding both hypoxaemia and excess hyperoxaemia.